The Effect Of Job Satisfaction On Employee Retention With Moderation Of Transformational Leadership Style At Bank Syariah Indonesia (Bsi), Mataram-Majapahit Sub-Branch Office (KCP) - Rodiatan Mardiyah; Khairul Hamim; Shofia Mauizotun Hasanah (Universitas Islam Negeri Mataram, 2025)
This study aims to investigate the effect of job satisfaction on employee retention and the moderating effect of transformational leadership style on the relationship between job satisfaction and employee retention at Bank Syariah Indonesia, Mataram-Majapahit Sub-Branch Office. The research adopts a quantitative approach with a survey design, utilizing a likert-scale questionnaire as the instrument to measure the variables studied. Data collected from all 32 employees at the Mataram-Majapahit Sub-Branch Office were analyzed using moderated regression analysis (MRA) with the assistance of SPSS software. The findings reveal that job satisfaction has a significant positive effect on employee retention, with a p-value < 0.05. However, transformational leadership style does not moderate the relationship between job satisfaction and employee retention, as indicated by a p-value > 0.05, despite an R² value of 89.2%. Based on these results, it is recommended that management enhance job satisfaction by focusing on key contributing factors and conduct regular evaluations of leadership styles to support employee retention. Furthermore, future researchers are encouraged to broaden the scope of study and incorporate additional variables to achieve a more comprehensive understanding. Keywords: Job Satisfaction, Employee Retention, Transformational Leadership Style